(3LdGA GdbdhH hCfS GdeMHhHs - (3eMeO Hf HjQ Ydj Hf EScfOQ GdHQcdj GdQhej , eMjj GdOjf, J (B981 (3g` s ((3eMeO Hf Ydi jYbhH GdCHTjfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd Gddjd hGdfgGQ NdaI def GQGO Cf jPcQ Ch GQGO eTchQkG s
(3BNQgG (B:s
(3Gddge jG HOjY GdSehGJ hGdCQV , jGPG GdLdGd hGdEcQGe JeJ gPg GdfSNI GdTQjaI GdefShHI Edi GdEeGe GdeMbb hGdMHQ GdeObb GdTgjQ HHQchfi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B123 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B252s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs